On non-uniformly parabolic functional differential equations - Simon, László; Jäger, Willi (Studia scientiarum mathematicarum Hungarica, 2007)
We consider initial boundary value problems for second order quasilinear parabolic equations where also the main part contains functional dependence on the unknown function and the equations are not uniformly parabolic.